Nitrogen Source and Rate Management Improve Maize Productivity of Smallholders under Semiarid Climates - Amanullah,; Iqbal, Asif; Ali, Ashraf; Fahad, Shah; Parmar, Brajendra (Frontiers in Plant Science, 2016)
Nitrogen is one of the most important factors affecting maize yield and profitability of smallholders under semiarid climates. Field experiments were conducted to investigate the impact of different N-fertilizer sources [urea, calcium ammonium nitrate (CAN) and ammonium sulphate (AS)] and rates (50, 100, 150 and 200 kg ha-1) on umber of rows ear-1 (NOR ear-1), number of seeds row-1 (NOS row-1), number of seeds ear-1 (NOS ear-1), number of ears per 100 plants (NOEP 100 plants-1), grain yield plant-1, stover yield (kg ha-1) and shelling percentage (%) of maize genotypes “Local cultivars (Azam and Jalal) vs. hybrid (Pioneer-3025)”. The experiment was conducted at the Agronomy Research Farm of the University of Agriculture Peshawar during summers of 2008 (year one) and 2010 (year two). The results revealed that the N treated (rest) plots (the average of all the experimental plots treated with N) had produced higher yield and yield components, and shelling percentage over N-control plots (plots where N was not applied). Application of nitrogen at the higher rate increased yield and yield components in maize (200 > 150 > 100 > 50 kg N ha-1). Application of AS and CAN had more beneficial impact on yield and yield components of maize as compared to urea (AS > CAN > urea). Hybrid maize (P-3025) produced significantly higher yield and yield components as well as higher shelling percentage than the two local cultivars (P-3025 > Jalal = Azam). We concluded from this study that application of N-fertilizer especially ammonium sulphate at the higher rate of 200 kg N ha-1 to hybrid maize could increase maize productivity and grower’s income in the study area. For the two local cultivars, application of 150 kg N ha-1 was found more beneficial than the recommended rate (120 kg N ha-1) in terms of higher yield, yield components and growers income.